Improving Tolerance Awareness and Attitude through Multicultural Value-Based Civics Learning at Smk Negeri 2 Palopo - Assafari, Amir Faqihuddin; Muharram Muharram; Darman Manda (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study aims to increase awareness and tolerance through multicultural value-based Civics learning at SMK Negeri 2 Palopo. This research uses a qualitative approach and collects data through observation, interviews, and documentation. The results showed that the design of the multicultural value-based Civics learning model developed involved the role of teachers and learners, as well as a supporting environment that includes racial, linguistic, religious, and gender diversity. The model is designed to increase mutual respect among learners through effective integration of cultural values in the learning process. This research found that the planning, implementation and evaluation processes of Civics learning have effectively integrated cultural values. Teachers have demonstrated their understanding and use of cultural values in their lesson planning, and have applied the principles of valid, objective, fair, and systematic assessment in evaluating the learning process. In addition, the implementation of learning activities has also taken into account values such as equality, democracy and tolerance, which are reflected in pre-activities, while-activities and post-activities. The results of this study indicate that the design of the multicultural value-based Civics learning model developed can increase awareness and tolerance among students. This research contributes to the development of a more inclusive and effective Civics learning model in increasing awareness and tolerance among students. The results of this study also show that the design of the multicultural value-based Civics learning model developed can increase awareness and tolerance among students